2000
DOI: 10.1002/pc.10188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemical composition and thermal stability of finishes on the compatibility between glass fiber and high melting temperature thermoplastics

Abstract: Experimental studies were made on the surface characteristics of glass fibers with two different finishes. The effects of the chemical composition and thermal stability of the finishes on the compatibility between glass fibers and high melting temperature thermoplastics were investigated. Thermogravimetric Analysis (TGA) was used to characterize the composition of surface finishes and their thermal stability. The chemical composition of surface finishes was investigated using a combination of X-ray photoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
(3 reference statements)
1
8
0
Order By: Relevance
“…The values of γ italiciitalicp and γ italiciitalicd for H 2 O and CH 2 I 2 are given in Table VII in the literature 32…”
Section: Resultsmentioning
confidence: 99%
“…The values of γ italiciitalicp and γ italiciitalicd for H 2 O and CH 2 I 2 are given in Table VII in the literature 32…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, they showed that the peak weight loss of the sizing on the fibres surface could occur at as much as 100°C lower than that of cast films. Gao et al [41] also investigated the thermal stability of silane only sizings on commercial glass fabrics using a combination of TGA, XPS and ToF SIMS. E-glass fabrics coated with either APTES or TG970 (an undefined silane containing amino functionality) were investigated.…”
Section: Thermal Analysismentioning
confidence: 99%
“…The binding energy of S 2p (170.5 eV) let us suppose that this element is present in a sulphate component. The C 1s spectra can be curve-fitted with three components: (i) a main component at a binding energy of 284.6 eV corresponding to C-H [13], (ii) a component at a binding energy of 286.5 eV corresponding to functional groups such as C-O and C-N [13], and (iii) a component at a binding energy of 288.7 eV corresponding to carboxylic groups (O-C@O) [13]. From the previous hypothesis, the absolute and relative percentages of these different components have also been determined.…”
Section: Xps Analysis Of the Fibre Surfacementioning
confidence: 99%
“…The impregnation ability should be then influenced by the sizing type applied on glass fibres and by the resin composition and thus by the interfacial adhesion [5][6][7][8][9][10][11]. Most of the researches were focused on the influence of silane coupling agents on polymer/glass interactions [6,[12][13][14][15][16]. However, commercial glass fibre sizings are multi-component mixtures in which the silane represents only a small fraction of the total mass deposited on the glass surface.…”
Section: Introductionmentioning
confidence: 99%